Species composition and richness of viable seed bank after fire events in Mount Ciremai National Park and Kuningan Botanic Gardens, West Java, Indonesia - Indriani Ekasari; Ronggo Sadono; Djoko Marsono; Joko Ridho Witono (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Ekasari I, Sadono R, Marsono D, Witono JR. 2021. Species composition and richness of viable seed bank after fire events in Mount Ciremai National Park and Kuningan Botanic Gardens, West Java, Indonesia. Biodiversitas 22: 3437-3447. Forest fire is an environmental disaster that can decline ecosystem function and restoration efforts must be considered to restore forest ecosystems after fire events. Natural regeneration using existing soil seed banks is a promising approach in restoration due to its advantage in terms of minimizing cost. This study aimed to examine the species composition and richness of germinable seed banks in several post-fire sites in Mount Ciremai National Park (MNCP) and Kuningan Botanic Gardens (KGB), West Java, Indonesia. One hundred fifty-eight soil samples were collected from the study sites representing fire events (i.e., four post-fire sites and one non-fire site), and soil depths (i.e., upper, middle, and lower). The collection of soil samples and identification of seedlings emergence were conducted from September 2019 to February 2020. Data were analyzed using ANOVA and correspondence analysis using SPSS Version 22. In total, 4626 emergence seedlings were recorded, belonging to 158 species and 58 families in which 41 families in the upper soil layer, 35 families in the middle soil layer, and 33 families in the lower soil layer. The results showed that Poaceae, Asteraceae, and Euphorbiaceae as the most dominant families. The upper soil layer of post-fire site 2018 had the highest species richness (R=11.98), while the lower soil layer of post-fire site 2012 had the lowest species richness (R=2.64). Our findings suggest that when carrying out restoration activities in post-fire areas, it is preferable to use native species that do not compete with species persisted in soil seed banks.